Re-Reading Bektashi Menakibnames: Transforming an Oral Text into the Prose = Pereskaz Legend Bektaši : preobrazovanie ustnogo teksta v prozu - Tashkyn, Ahmet (Chabaršy. Dintanu serijasy, 2015)
This presentation proposes to shed light on menakibname texts that reached to Anatolia via Turkistan and Horasan. These texts narrate the studentship, mentors, journeys, doctrines, the other sheiks and students that create his life, individual and social relationships, and lastly psychological developments of the characters that are centred. Presentation asserts that menakib texts have a unique language and semantic world that should be explained. To fulfil this, the presentation also offers to read the menakib texts by always considering the communities that engage in these texts. Because menakibnames, which are read and narrated among communities, have been transferred to proses in time, some of their oral text features have become less visible. Eventually, Bektashi menakibnames have not received necessary interest and these couldn’t be presented to scientific world to be benefited.